2010
DOI: 10.1177/0192513x10390858
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Color Consciousness in Black Families: Exploring Family Processes and Women’s Experiences With Colorism

Abstract: Family is regarded as a powerful force in the lives of Black Americans. Often-times, families function as an agent of socialization that counters racism. At the same time, however, Black families can perpetuate skin tone consciousness and bias, or colorism . Although there is an extensive body of revisionist literature on Black families and a growing body of scholarship on the contemporary nature of colorism, there is a dearth of literature addressing the role of Black families in relation to colorism. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 24 publications
6
72
1
Order By: Relevance
“…In contrast, more positive marital attitudes had a weaker dampening effect on risky sexual behavior for darker skin individuals than lighter skin individuals as darker skin individuals may view marriage as a less attainable option. Such findings are consistent with evidence suggesting that darker skin individuals, particularly women, may be losing hope that committed relationships and marriage are attainable (Awad et al 2014; Boylorn 2012; Ferdinand 2015; Wilder and Cain 2011), therefore marriage and cohabitation attitudes do little to offset their engagement in risky sexual behavior. All these significant links emerged among specific racial/ethnic minority groups: African Americans and Asians.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, more positive marital attitudes had a weaker dampening effect on risky sexual behavior for darker skin individuals than lighter skin individuals as darker skin individuals may view marriage as a less attainable option. Such findings are consistent with evidence suggesting that darker skin individuals, particularly women, may be losing hope that committed relationships and marriage are attainable (Awad et al 2014; Boylorn 2012; Ferdinand 2015; Wilder and Cain 2011), therefore marriage and cohabitation attitudes do little to offset their engagement in risky sexual behavior. All these significant links emerged among specific racial/ethnic minority groups: African Americans and Asians.…”
Section: Discussionsupporting
confidence: 85%
“…In particular, Hamilton et al (2009), in a study of 329 young black women found that light skin tone was associated with approximately a 15 % greater probability of marriage. In other studies including focus groups of Black women, evidence suggests that darker skin individuals may be losing hope that committed relationships and marriage are attainable (Boylorn 2012; Ferdinand 2015; Golden 2007; Wilder and Cain 2011) given the relationship between skin tone and perceptions of beauty. For example, a participant in a recent qualitative study illustrated this point stating “None of the boys wanted to marry me because I was too dark and they were already asking me “you know your children are going to come out really, really dark and that's not good.” But my light skinned friend got married to a different boy every day.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we reviewed and offered evidence of gender (and to a lesser extent class) differences among African Americans and how these might affect the terms of social exchange. Further, drawing on the colorism literature (Burton et al, ; Hunter, ; Wilder & Cain, ), we showed that skin tone is a unique form of exchange capital in intimate relationships among African Americans.…”
Section: Moving Forward: Implications and Avenues For Social Exchangementioning
confidence: 68%
“…Moreover, research has acknowledged that women are more profoundly affected by issues of skin tone because it is inextricably tied to cultural values regarding beauty (Hill, ; Hunter, ). A gendered skin‐tone preference has been illustrated among male peers who reported a preference for lighter‐skinned partners (Bond & Cash, ; Hunter, ) and within the family context, where lighter‐skinned girls received preferential treatment (Landor et al, ; Wilder & Cain, ). As a result, individuals learn that certain physical features are evaluated more favorably than others and are more beneficial in numerous aspects of life, including intimate relationships.…”
Section: Terms Of Social Exchange From a Colorism Perspective: A Focumentioning
confidence: 99%
“…Ironically, between 2000 and 2010, the south, in spite of its history of a defiant stance against the federal order requiring previously segregated public schools to admit black school children, legalized bans against black and white interracial marriage, and the racial terror and violence of the Ku Klux Klan, saw a 49% increase in the population of two or more races (Jones & Bullock, 2012 Darity (2006, 2007), who, after controlling for productivity-linked characteristics, discovered greater gaps in wages between darker-skinned blacks and whites than between lighter-skinned blacks and whites, that is, black people with lighter complexions earned more money than darker-skinned blacks. Colorism is an intraracial system of inequality in which the allocation of privileges and disadvantages is based on skin color (Hunter, 2002(Hunter, , 2005Wilder & Cain, 2011; Ward, Robinson-Wood, & Boadi, in press). Colorism is a problem that exists today (Ward, Robinson-Wood, & Boadi, in press).…”
mentioning
confidence: 99%